Creative Process and Documentation: digital archiving and music theatre - Mota, Marcus; Rangel, Alexandre (Revista Brasileira de Estudos da Presença, 2020)
This paper presents a discussion and research results related to the development of an online database for musical theater productions . The increase of musical theatre productions creates the need to propose ways to archive materials from various media. The database assembled for the musical David, created at the Dramaturgy Laboratory of the University of Brasilia in 2012, was studied as a methodological example.